2020
DOI: 10.3390/coatings10020129
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Decorated with Titanium Nanoparticles to Reinforce the Anti-Corrosion Performance of Epoxy Coating

Abstract: Graphene oxide–titanium (GO-Ti) composite materials were fabricated using GO as a precursor and then anchoring nano titanium (Nano-Ti) particles on GO sheets with the help of a silane coupling agent. Then, the coating samples were prepared by dispersing GO, Nano-Ti particles, and GO-Ti in an epoxy resin at a low weight fraction of 1 wt %. The GO-Ti composites were investigated by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 35 publications
(22 reference statements)
2
27
0
Order By: Relevance
“…Graphene ( Figure 4 ), with its most important derivative graphene oxide (GO), was probably the first compound of this broad family proposed to manufacture high-performance nanocomposites due to its unique shape (two-dimensional crystals with an average thickness of about 1 −10 m and diameter 0.5–5 μm) and outstanding electrical (with a conductivity of 6 × 10 5 S/m), mechanical (in terms of tensile strength and especially Young’s modulus, the latter being equal to 1.1 TPa), thermal (conductivity around 5000 W/m·K), and barrier properties [ 16 ]. Its addition can provide a reinforcing effect to the epoxy matrix and multifunctionality for the most varied engineering applications (anticorrosive coatings, structural adhesives, thermal conductors) at lower costs than the more expensive carbon nanotubes, to fabricate electric and electronic devices, and also in the field of fiber-reinforced polymers [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. GO nanosheets, characterized by an extremely high surface area (~2630 m 2 /g), may represent a feasible alternative to functionalized/unmodified carbon nanotubes also when enhancements in mechanical, electrical, and thermal properties are mostly required for a conventional epoxy [ 24 ].…”
Section: Nanofillers For Epoxy Resinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene ( Figure 4 ), with its most important derivative graphene oxide (GO), was probably the first compound of this broad family proposed to manufacture high-performance nanocomposites due to its unique shape (two-dimensional crystals with an average thickness of about 1 −10 m and diameter 0.5–5 μm) and outstanding electrical (with a conductivity of 6 × 10 5 S/m), mechanical (in terms of tensile strength and especially Young’s modulus, the latter being equal to 1.1 TPa), thermal (conductivity around 5000 W/m·K), and barrier properties [ 16 ]. Its addition can provide a reinforcing effect to the epoxy matrix and multifunctionality for the most varied engineering applications (anticorrosive coatings, structural adhesives, thermal conductors) at lower costs than the more expensive carbon nanotubes, to fabricate electric and electronic devices, and also in the field of fiber-reinforced polymers [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. GO nanosheets, characterized by an extremely high surface area (~2630 m 2 /g), may represent a feasible alternative to functionalized/unmodified carbon nanotubes also when enhancements in mechanical, electrical, and thermal properties are mostly required for a conventional epoxy [ 24 ].…”
Section: Nanofillers For Epoxy Resinsmentioning
confidence: 99%
“…Often, the functionalization of the surface of a nanofiller is achieved by treatment with silane solutions, such as in the case of nanoclays [ 75 ], graphene [ 92 , 93 ], boron nitride [ 87 ], and SiO 2 nanoparticles [ 64 ]. The silane can also act as a coupling agent, allowing the graft of other chains/compounds on the surface of the nanofiller, synergistically improving the nanocomposite performance [ 22 , 94 ].…”
Section: Production Of Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al [22] reported that basalt flake modified epoxy coatings that were incorporated with 3% nanosilica showed excellent chemical and mechanical performance. Yuan et al [23] reported that the incorporation of titanium nanoparticle modified graphene oxide significantly improved the corrosion and wear resistance of the epoxy coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Metal corrosion has become a very serious issue. The global annual corrosion cost is estimated to be around 3–5% of the GDP [ 13 ]. Coating on metal substrates to reduce corrosion is widely used as an effective solution.…”
Section: Introductionmentioning
confidence: 99%